Detection of pig residue in fish feedstuffs and fish stomach content using polymerase chain reaction for halal certification - Ahemad Sade (Jabatan Perikanan Malaysia, 2015)
Samples preparation and processing methods have been determined. Stomach contents were processed in the field, preserved in 80% ethanol and kept in -20°C until DNA extraction. Feeds were kept in 4°C until DNA extraction. Suitable extraction and PCR kits for pig residues detection from freshwater feed pellet and tilapia (Oreochromis niloticus) stomach content tissue samples had been determined. Feed pellet and stomach content tissues DNA were extracted using spin-column method (Vivantis GF-1 Tissue DNA Extraction Kit) and subjected to PCR amplification using Hai Kang Watcher Porcine PCR Kit and Hai Kang Hunter Porcine RT-PCR Kit for end-point and real-time PCR, respectively. Even though the DNA was degraded, which were as expected, DNA from both samples was able to be amplified. The current preliminary result is a potentially reliable technique for pig residues detection in willful or fraudulent feed substitution or contamination in freshwater fish farming for the purpose of Halal certification scheme.